Economic analysis of the rules and regulations of the World Trade Organization - Saggi, Kamal (World scientific studies in international economics, 2019)
This book examines how international economic activities are organized and regulated through scientific and institutional frameworks. It explores the roles of international organizations, legal systems, and governance structures in shaping global economic relations. By integrating perspectives from economics, law, and political science, the work offers insights into the dynamics and challenges of managing the global economy.